Perancangan Sistem Informasi Pendistribusian Beras Miskin Pada Kantor Kelurahan Sirandorung Berbasis Web - Zuraidah, Zuraidah; Nasution, Marnis; Harahap, Syaiful Zuhri; Juledi, Angga Putra (Universitas Labuhanbatu, 2022)
The development of today's increasingly advanced technology such as the use of computers has become popular in the community, the use of computers is very important because the computer is a tool in carrying out data processing activities, so that a job can be completed properly. How the distribution of rice for the poor can work properly using this application. The purpose of the study is to assist the process of distributing rice for the poor at the Sirandorung Village Office. The system analysis stage is a very important stage because errors at this stage will result in errors in the next stage. In analyzing the system, several methods are used, among others. Based on the results of research and discussion that the results of the analysis of the implementation of the distribution of rice for poor households (Raskin) in Sirandorung Village, Rantau Utara District, Labuhanbatu Regency, the implementation is still not precise and has not been implemented properly. This is based on the analysis above and based on the results of questionnaires and interviews with researchers from the Sirandorung sub-district office. All people in the Sirandorung sub-district should be collected and provided with detailed information about the Raskin program so that there is no misunderstanding or receiving inaccurate information about Raskin.